2008
DOI: 10.1016/j.apsusc.2007.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Understanding barium sulfate precipitation onto stainless steel

Abstract: This paper investigates the influence of barium sulfate scaling and scaling inhibitors on the electrochemical behaviour of stainless steel. The results of a synchrotron radiation grazing incidence X-ray diffraction (SR-GIXRD) and electrochemical impedance spectroscopy (EIS) study on stainless steel shows that different scaling inhibitors interact uniquely with the substrate when barium sulfate is precipitated on the electrode surface. The main effect of the substrate in the presence of inhibitor is a tendency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Kucher et al (2008) have quantitatively determined the transient increase of the crystalline mass during barium sulfate precipitation and found that the nucleation rate does not depend on the initial free lattice ion ratio. In context with oil and gas processing, Jones et al (2008), Mavredaki et al (2011) and Webster et al (2014) have investigated surface deposition Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/ces and its prevention on stainless steel due to barium sulfate precipitation. In the free jet micro mixer SAXS study by Marmiroli et al (2009Marmiroli et al ( , 2010, calcium carbonate particles are detected in the range of microseconds after mixing.…”
Section: Introductionmentioning
confidence: 99%
“…Kucher et al (2008) have quantitatively determined the transient increase of the crystalline mass during barium sulfate precipitation and found that the nucleation rate does not depend on the initial free lattice ion ratio. In context with oil and gas processing, Jones et al (2008), Mavredaki et al (2011) and Webster et al (2014) have investigated surface deposition Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/ces and its prevention on stainless steel due to barium sulfate precipitation. In the free jet micro mixer SAXS study by Marmiroli et al (2009Marmiroli et al ( , 2010, calcium carbonate particles are detected in the range of microseconds after mixing.…”
Section: Introductionmentioning
confidence: 99%
“…In an oil and gas processing context, there are examples of in situ diffraction studies of BaSO 4 formation [13][14][15][16][17][18][19]. However, these have either examined bulk solution precipitation rather than surface deposition on stainless steel [13][14][15], or have acquired data over too long a time frame to make a meaningful assessment of the kinetics of rapid deposition on stainless steel [16][17][18][19].…”
Section: Introductionmentioning
confidence: 96%
“…However, these have either examined bulk solution precipitation rather than surface deposition on stainless steel [13][14][15], or have acquired data over too long a time frame to make a meaningful assessment of the kinetics of rapid deposition on stainless steel [16][17][18][19]. Based on the results of Mavredaki et al [6,[17][18][19], depending on the nature of the waters used and the temperature, a time resolution of a few seconds is required to establish a growth curve during uninhibited BaSO 4 scale formation at 25°C.…”
Section: Introductionmentioning
confidence: 98%
“…The X-Ray Synchrotron Diffraction measurements of barium sulphate precipitation made by other researchers, have lead to determination of the main faces of barite [1,2]. Additionally SXRD was used in order to study the effect of inhibitors such as nitrilotriacetic acid (NTA) and nitrilomethylenephosphonic acid (NTMP) on barite precipitation at 80°C [3]. These two inhibitors were investigated for their effect on the barite formation on stainless steel.…”
Section: Introductionmentioning
confidence: 99%